KI Increases Tomato Fruit Quality and Water Deficit Tolerance by Improving Antioxidant Enzyme Activity and Amino Acid Accumulation: A Priming Effect or Relief during Stress? - Jucelino de Sousa Lima; Otávio Vitor Souza Andrade; Everton Geraldo de Morais; Gilson Gustavo Lucinda Machado; Leônidas Canuto dos Santos; Eduarda Santos de Andrade; Pedro Antônio Namorato Benevenute; Gabryel Silva Martins; Vitor L. Nascimento; Paulo Eduardo Ribeiro Marchiori; Guilherme Lopes; Eduardo Valério de Barros Vilas Boas; et al. (Plants, 2023)
A water deficit can negatively impact fruit yield and quality, affecting critical physiological processes. Strategies to mitigate water deficits are crucial to global food security. Iodine (I) may increase the efficiency of the antioxidant system of plants, but its role against water deficits is poorly understood. This study aimed to evaluate the effectiveness of I in attenuating water deficits and improving fruit quality, investigating whether metabolic responses are derived from a “priming effect” or stress relief during water deficits. Tomato plants were exposed to different concentrations of potassium iodide (KI) via a nutrient solution and subjected to a water deficit. A water deficit in tomatoes without KI reduced their yield by 98%. However, a concentration of 100 μM of KI increased the yield under a water deficit by 28%. This condition is correlated with increased antioxidant activity, photosynthetic efficiency improvement, and malondialdehyde reduction. In addition, the concentration of 100 μM of KI promoted better fruit quality through antioxidant capacity and a decline in the maturation index. Therefore, KI can be an alternative for attenuating water deficits in tomatoes, inducing positive responses during the water deficit period while at the same time improving fruit quality.